Babesia microti in a Canadian blood donor and lookback in a red blood cell recipient. Issue 3 (31st August 2021) - Drews, Steven J.; Van Caeseele, Paul; Bullard, Jared; Lindsay, L. Robbin; Gaziano, Teresa; Zeller, Michelle P.; Lane, Debra; Ndao, Momar; Allen, Vanessa G.; Boggild, Andrea K.; O'Brien, Sheila F.; Marko, Daniel; et al.
Abstract: Background and Objectives: We describe the third documented case of autochthonous human babesiosis in Canada and the second in a Canadian blood donor. Materials and Methods: Multiple laboratory investigations were carried out on the donor and the immunocompromised recipient of an associated, potentially infectious red blood cell product. Results: The donor had not travelled except for outdoor exposure in south‐eastern Manitoba, followed by illness and hospital admission. The donor had a notable parasitaemia, positive for Babesia microti using whole blood nucleic acid testing (NAT). The recipient was negative for B. microti by both serology and NAT. Conclusion: There was no evidence of transfusion‐transmitted babesiosis.